Neutrophil–lymphocyte ratio as an early predictor for patients with acute paraquat poisoning: A retrospective analysis - Cao, Zong Xun (Medicine (Baltimore), 2019)
This retrospective study aimed to investigate whether the neutrophil–lymphocyte ratio (NLR) can be used as an early predictor of 90-day survival in patients with acute paraquat (PQ) poisoning. This study enrolled 105 patients with acute PQ poisoning admitted from May 2012 to May 2018. Kaplan–Meier curve, receiver operating characteristic curve, and Cox proportional hazards regression analyses were used to investigate the predictive value of NLR for 90–day survival of patients with acute PQ poisoning. The 90-day survival rate was 40.95% (43/105). Survivors had lower NLR (P <.001), which was an independent predictor of 90-day survival according to the Cox proportional hazard regression analyses. The area under the NLR curve was 0.842 (95% CI: 0.767–0.917, P <.001) in predicting 90-day survival. Our findings showed that low NLR was a valuable early predictor of 90-day survival in patients with acute PQ poisoning.